Pemanfaatan Tanaman Hias Sebagai Media Pembelajaran Biologi - Lia Angela; Husnin Nahry Yarza; Toni Haryanto; Nisa Novita Putri (Symbiotic: Journal of Biological Education and Science, 2020)
The research aims to determine the types of ornamental plants found in the SMP Negeri 11 Sungai Penuh school environment. This research was conducted in two stages: the first stage was identifying ornamental plant species found in the school yard and made as learning media in the form of a photo album. The second stage applies the identification results in the form of photo album media in biology learning. The method used in this study, in the first stage uses descriptive analysis with survey methods and the second stage uses quantitative analysis. The instruments used in this study were questionnaires, key books of determination and photos of plants from internet references. The results of this study were found 19 types of ornamental plants found in the school yard of SMP Negeri 11 Sungai Penuh and the dominant ornamental plant is the type of Araceae. The results of student responses to the ornamental plant media obtained an average value of 89.3% with a very good category.